The Forgotten City : Rethinking Digital Living for Our People and the Planet - Allmendinger, Philip, 1968- (Book collections on Project MUSE., 2021)
Phil Allmendinger takes a critical approach to the role of 'smart' in future cities and the relationship with city development. Considering how technology can support active citizenship, he challenges the commercial drivers of big tech and warns that these, not developments for 'social good', may dominate.